Analisis Perhitungan Harga Pokok Produksi Menggunakan Metode Job Order Costing : (Studi Kasus Pada PT. Anugrah Adi Jaya) - Karmana, Sundari Ainun Putri; Rosmiati, Mia (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Abstract: Calculation of the precise cost of goods manufactured is significant for the company. It will be the essential key for determining the selling price. Commonly, the company is less attention to detail in calculating applied factory overhead costs. Hence, the company will find it difficult to examine whether the company is profit or loss. This research was conducted at PT Anugrah Adi Jaya that is a business engaged in clothing convection. The production process is carried out by order. This study aims to determine the result of the calculation of the cost of manufactured using the job order costing method with the study case of 35.000 pcs of PON hats. According to the research question and the discussion, the calculation of the cost of manufactured based on the company is Rp.20.081/pcs. Meanwhile, if using the job order costing approach by applying factory overhead cost is Rp.17.373/pcs. Therefore, the company should calculate all elements of the factory overhead cost and use the job order costing mechanism, as well as record the additional notes using the cost of goods ordered card.